Determinants of Mobile Banking Adoption Intention among Rural Non-Users in Indonesia: An Extended UTAUT Model - Hendra Prabha; Anderes Gui (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: This study examines the determinants of mobile banking adoption intention among rural non-users in Indonesia by applying an exended Unified Theory of Acceptance and Use of Technology (UTAUT) model. Methods: A cross-sectional survey was conducted among 397 rural smartphone owners aged 20–59 years who had never used mobile banking, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS, with 10,000 bootstrap subsamples and one-tailed significance tests. Results: The findings indicate that awareness, facilitating conditions, and performance expectancy exert positive and significant effects on behavioral intention, whereas technology anxiety exerts a significant and substantively meaningful negative effect (f² = 0.027). Perceived risk also shows a significant negative effect, but its effect size is negligible (f² = 0.016), indicating only a marginal practical contribution despite statistical significance. By contrast, effort expectancy and social influence do not show significant effects. The model explains a moderate proportion of variance in behavioral intention (R² = 0.568) and demonstrates an acceptable model fit (SRMR = 0.049). Conclusion: The results suggest that mobile banking adoption intention among rural non-users is shaped more by perceived usefulness and enabling conditions, with technology anxiety acting as the most practically important psychological barrier and perceived risk playing a comparatively minor role. In contrast, ease of use and social influence appear to be less decisive factors. These findings provide empirical support for inclusion-oriented outreach strategies that prioritize anxiety reduction and confidence building, alongside clear value communication and structured onboarding support.